Ecological Characteristics of Ventenata dubia in the Intermountain Pacific Northwest. (March 2015) - Wallace, John M.; Pavek, Pamela L. S.; Prather, Timothy S.
Abstract: Ventenata dubia is an exotic winter annual grass that has invaded Conservation Reserve Program (CRP) lands, improved pastures, intensively managed hay fields, and rangelands within the Intermountain Pacific Northwest (PNW). Currently, producers are attempting to develop V. dubia management strategies with little knowledge of its life history traits. We conducted several studies to characterize V. dubia life history patterns. Preliminary germination trials were completed to describe primary and secondary dormancy characteristics. Field studies were conducted to evaluate (1) seed bank persistence patterns, (2) seedling emergence patterns under V. dubia litter, and (3) seedling emergence and phenological development patterns within timothy hay, CRP, and rangeland habitats. Preliminary germination trials suggest that the after-ripening period required for loss of dormancy does not exceed 30 d and that dormancy breakdown peaks at approximately 90 d, after which germination occurs over a wide range of temperatures (9 to 29 C). A small fraction (< 1%) of the seed bank remained germinable up to 3 yr after burial at 2 cm depth in a grassland habitat. Seedling emergence and survival was significantly greater under high V. dubia litter layers (100% cover) compared with bare surface during the drier study year because of higher soil moisture levels maintained under litter. Across habitat types, mean seedling emergence (50% of total) occurred between 33 and 94 growing degree days (GDD) after soil moisture rose above the permanent wilting point in the fall. Seedling emergence periodicity varied among habitat types in relation to spring seedling emergence, ranging from 0 to 13% of total emergence per year. Phenological development differed across sites and years by up to several hundred GDDs but was closely aligned to Julian days. This collection of studies improves our understanding of V. dubia life history traits and will aid integrated weed management strategies in the Intermountain PNW.